2019
DOI: 10.1080/07391102.2019.1696705
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential entry inhibitors for emerging Nipah virus by molecular docking and chemical-protein interaction network

Abstract: Nipah Virus (NiV) is a newly emergent paramyxovirus that has caused various outbreaks in Asian countries. Despite its acute pathogenicity and lack of approved therapeutics for human use, there is an urgent need to determine inhibitors against NiV. Hence, this work includes prospection of potential entry inhibitors by implementing an integrative structure-and network-based drug discovery approach. FDA-approved drugs were screened against attachment glycoprotein (NiV-G, PDB: 2VSM), one of the prime targets to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 109 publications
(129 reference statements)
0
7
0
Order By: Relevance
“…Structure-based molecular docking is conceivably the most reliable and widely implemented approach in the early phase of drug discovery ( 46 ). In our docking results, the top 5 ranked small molecules including Nisin, Enalapril maleate (Vasotec), Mangafodipir Trisodium, Raltitrexed (Tomudex), and Iron sucrose had high docking score with CHRNB4 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Structure-based molecular docking is conceivably the most reliable and widely implemented approach in the early phase of drug discovery ( 46 ). In our docking results, the top 5 ranked small molecules including Nisin, Enalapril maleate (Vasotec), Mangafodipir Trisodium, Raltitrexed (Tomudex), and Iron sucrose had high docking score with CHRNB4 protein.…”
Section: Discussionmentioning
confidence: 99%
“…(3) molecular docking-all ligands were docked into the respective ligand-binding sites using the QuickVina v 2.0 [50] software, a docking tool that accelerates AutoDock Vina software [51] by implementing an already benchmarked (on CCDC/ASTEX dataset) molecular docking approach [37]. The small molecules that bind to all the three viral proteins (NiV-G ∩ NiV-F ∩ NiV-N) were considered multitarget inhibitors.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Our group has developed a resource of multitargeted putative therapeutics and epitopes for NiV drug discovery as well [35]. Additionally, several small-molecule inhibitors were identified by our group using QSAR [36] and molecular docking-based studies [37]. In our previous study [37], we have identified small-molecule FDA-approved drugs as potential inhibitors of NiV-G using an ensemble of molecular docking and analysis of the chemical-protein interaction network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their natural existence, easy availability, extensive antimicrobial, antiviral, antivirulence, and pharmacological properties, the application of plant-derived products and bioactive phytochemicals in modern medicine has gained momentum among researchers (Chadha et al, 2021;Chadha et al, 2022a). Numerous in silico and pharmacoinformatics-based reports have predicted the effectiveness of phytochemicals and other drugs against SARS-CoV-2, Ebola, and Nipah virus (Kwofie et al, 2019;Pathania et al, 2019;Choudhury et al, 2021;Kumar et al, 2021a). On similar lines, we employed a comprehensive in silico approach to identify phytochemicals that could potentially act as inhibitors against poxviruses for repurposing them against the MPXV.…”
Section: Introductionmentioning
confidence: 99%